Deciphering "Educational Hubs" Strategies: Rhetoric and Reality - Kinser, Kevin; Lane, Jason (International Higher Education, 2010)
Many governments in the Middle East and Southeast Asia have repositioned them as "education hub." Four realities of education hub strategies are described. First, institutions in education hubs are not always in close proximity. Second, there are education hubs that are primarily lead by the nongovernmental entities as sponsors though with the support of the government. Third, all education cities are designed to be education hubs, but not vice versa. Fourth, educational hubs are driven by the supply-side, rather than domestic demand.